Pengembangan Game 3D Warship Operation Trikora - Mohamad Faisal Amir; Wibisono Sukmo Wardhono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Many of the operation Trikora stories are only stored in the histroy museum. So many people unaware of the armed conflict and the heroic battles that happen in the operation. Video game is an interesting way to tell the story of Operation Trikora then the game Warship Operation Trikora was made. Game design is the process of making the content and rules of a game. Iterative process method in game design that is making prototype, played, and refined repeatedly before considered final. 3D graphics means to achieve generation of fictional worlds in the player's imagination that grow from a comprehension of the 3D representations so forming immersive video game. To build a narrative gameplay, a game designed with creating a battle story screnarios in form of a steps that consists of a collection of events in the game. Inside the the battle story scenarios there is events in the form of task for the player, it is called an objectives. Based on the tasks, objective can be grouped into 5 types that is area scope, location pointer, attack the ship, attack the plane, attack the pillbox. Iterative desgin methods are used to test objectives when it's applied in a game by creating a rapid prototype, performing playtest, and revised. This activity repeatedly until the game is considered decent to be implemented. Implementation of 3D characters needed to create assets of characters that involved in the battle story scenario. There are 7 types of characters in the form of ships, aircraft, and pillbox. Implementation of the scenes is done with Unity game engine by decorating environtments and placing game objects so that create the scenes forming an unique menu and stages. Each scenes is connected to each other. Script are implemented to create battle scenarios in digital version of game with C# programming language. Warship Operation Trikora has functional 100% working as expected both from scene flow, character mechanics, and objectives. Comparison of respondents between before playing this game and during playing this game, showed an knowledge average increase by 8.33 out of 10 knowledge presented in the game. Based on usability testing, 9 out of all game usability heuristics are included in good criteria and 8 out of all gameplay heuristics also included in good criteria.